Alveolar macrophages maintain tissue localization and gain enhanced anti-tumor activity in Lewis lung carcinoma-reprogrammed lung microenvironment - Ren, Mengfei; Dou, Jiaxiang; Yue, Qian; Ma, Liqin; Yu, Hang; Shang, Shengwen; Wang, Shijie; Wang, Jian; Li, Tingting; Li, Fengqi (Frontiers in Immunology, 2025)
The role of alveolar macrophages (AMs) in lung carcinogenesis has been extensively studied, yielding significant insights. However, the status of AMs in tumor-bearing lungs remains incompletely characterized. Using orthotopic Lewis Lung Carcinoma (LLC) mouse models, we found that tumors induced an inflammatory extra-tumoral lung microenvironment (ETLME), distinct from the immunosuppressive tumor microenvironment (TME). T cells with an exhaustion phenotype and tumor-associated macrophages (TAMs) mainly accumulated in the TME rather than the ETLME. Surprisingly, AMs were absent from the tumor lesions and remained in the lung tissues, but they displayed a more active dynamic balance between proliferation and death in ETLME. Furthermore, AMs presented an activated phenotype characterized by upregulation of CD11b and downregulation of Siglec-F, elevated expression of inflammatory genes, and enhanced phagocytic and efferocytotic activity. Notably, AMs in ETLME retained their lipid metabolism capacity and responsiveness to external stimuli. More importantly, LLC-experienced AMs display enhanced anti-tumor ability. These findings indicate that AMs maintain their tissue localization and functional integrity within the ETLME.